How many cancer deaths could New Zealand avoid if five‐year relative survival ratios were the same as in Australia?. (25th February 2015) - Sandiford, Peter; Abdel‐Rahman, Manar E.; Allemani, Claudia; Coleman, Michel P.; Gala, Geeta
Abstract Aim: To determine how many Māori and non‐Māori deaths might have been avoidable if cancer survival in New Zealand were as high as in Australia. Methods: Age‐sex‐tumour specific five‐year relative survival ratios were calculated for cancer patients diagnosed with 27 tumour sites (representing about 92% of all cancers) in 2006–10. These were used to estimate the number of Māori, non‐Māori and total deaths (and proportion of excess deaths) that would have been avoidable within five years of diagnosis had New Zealand's relative survival been equivalent to Australia's. Results: A total of 3, 631 cancer deaths (726/year; 13.4% of excess deaths) could have been avoidable. Among 25 tumours where ethnic‐specific results were estimated, there were 851 potentially avoidable deaths in Māori (24.9%) and 2, 758 in non‐Māori (11.8%). Breast, bowel, lung and prostate tumours made up 64% of avoidable deaths. Those with the highest proportions of avoidable deaths were thyroid (44.7%), prostate (35.5%), breast (30.0%) and uterus (23.5%). More than 50% of Māori melanoma, prostate, testis and thyroid cancer deaths were avoidable. Conclusion: A significant number of cancer deaths could be avoidable if New Zealand achieved Australia's relative survival ratios. The proportion is much higher for Māori than for non‐Māori. Implications: There is considerable scope to improve cancer outcomes in New Zealand.